The selected holistic concept of water management problems - Sandner, Jan (Studia Ecologiae et Bioethicae, 2006)
The Author, in the article, discusses proper water management problems. He presents the primary causes resulting in the degradation of water relations in the form of regular occurrences of floods or dry spells in Europe. In the article, degradation of water relation problems taking place in our country is compared to those in Germany or Austria. He points to the need for systematic teaching of basic environmental subjects within the holistic concept constituting a tool in shaping pro-ecological consciousness.